2018
DOI: 10.2507/ijva.4.2.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Perception of educators on the mediation role of ease of use in predicting the relationship between teacher competence and use behaviour

Abstract: This paper analyses the relationship between the teacher technology competence and their use of technology under the mediating influence of ease of use. The paper presents a set of results that are empirically tested on a sample of 387 high school and higher secondary school teachers from across 14 districts in Kerala, a southern state in India. A majority of these respondents had a teaching experience of more than eleven years and had been using computers for more than five years. The results reveal that tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[20] found that for teachers to adopt or use ICT, teachers need to see the necessity of making such changes and how that would affect their practice and students learning. Another study stated the mediation effect of ICT teacher competency and ease of use of technology [21]. This technology adoption by teachers would reflect in their perception of ease of use of ICT tools and their actual use behavior.…”
Section: Ease Of Usementioning
confidence: 99%
“…[20] found that for teachers to adopt or use ICT, teachers need to see the necessity of making such changes and how that would affect their practice and students learning. Another study stated the mediation effect of ICT teacher competency and ease of use of technology [21]. This technology adoption by teachers would reflect in their perception of ease of use of ICT tools and their actual use behavior.…”
Section: Ease Of Usementioning
confidence: 99%
“…Timoštšuk, Kikas & Normak, 2016). while limited investigation on the relationship between causes of teacher test anxiety and other approaches of anxiety (Von der Embse et al, 2018;Maulana, Opdenakker & Bosker, 2016;Kurian, Ramanathan & Andrlic, 2018).…”
mentioning
confidence: 99%